KONSELING PASTORAL SEBAGAI KEBUTUHAN PENDAMPINGAN BAGI ORANG TUA USIA LANJUT - Yohan Brek; Christine Lois Hadi Waluyo (POIMEN Jurnal Pastoral Konseling, 2022)
This research is motivated by intense communication with several elderlies which then encouraged the researcher to take a deeper look into their existence. The results of the study indicate that there is a communication gap in the family that causes elderlies to experience loneliness. Therefore, this study is about how elderlies can overcome the lonely atmosphere experienced with self-motivation, perception of life, and a relationship with God as a companion who can overcome loneliness. The purpose of this study is to analyze the causes of the elderly’s loneliness, self-motivation needs, perceptions about life, and the extent of their relationship with God. This research uses a qualitative method and descriptive approach, data are collected through the interview technique. Qualitative analysis is taken from the data that has been interpreted and provided with information and studies. The research has shown that the communication gap in the family does impact the self-motivation of elderlies and their perceptions of God. Therefore, pastoral counseling is indispensable.